Literasi Digital dan Pendidikan Karakter dalam Pembelajaran Daring : Analisis Kualitatif Video Edukasi Bahasa Indonesia di Youtube - Fira Fausila; Muhammad Akhir; Anzar Anzar (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
The development of digital technology has driven significant changes in learning practices, including Indonesian language learning, which increasingly utilizes online platforms such as YouTube. In this context, digital literacy is not only related to the technical ability to access information but also encompasses ethical, critical, and character-building aspects of students. This study aims to analyze the integration of digital literacy and character education values in online learning through Indonesian language educational videos on YouTube. The research employed a qualitative approach using content analysis methods. The research data consisted of Indonesian language learning videos selected purposively based on the relevance of the material, channel popularity, and consistency of educational content. The findings reveal that Indonesian language learning videos on YouTube contain various character education values, such as responsibility, academic honesty, hard work, independence, tolerance, and communicative attitudes. These values are integrated through the presentation of materials, the use of polite language, contextual examples, and reflective invitations that encourage students to think critically. In addition, aspects of digital literacy are reflected in the ability of video content to guide students toward the wise, selective, and responsible use of digital media. However, the study also identified several limitations, particularly the lack of systematic explicitness of character values and the suboptimal two-way interaction between educators and students.